P-LUM-08: Endoscopic ultrasound-guided fine needle aspiration: A new modality to diagnose peritoneal tuberculosis in the presence of decompensated cirrhosis – a case series - Daswani, Ravi (Endosc Ultrasound, 2017)
The gold standard for diagnosis of peritoneal tuberculosis is growth of Mycobacterium tuberculosis on ascitic fluid or peritoneal culture. Due to the nonspecific signs and symptoms of disease, its early diagnosis is difficult, especially in patients with decompensated cirrhosis. The reported sensitivity of ascitic fluid is low, and to obtain tissue for peritoneal biopsy in patients with cirrhosis is difficult. Thus, there is an urgent need to explore newer diagnostic modalities, especially those that can provide perioneal tissue by less invasive means. Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) is a good alternative to obtain peritoneal tissue for establishing the diagnosis of peritoneal tuberculosis (TB). We hereby report the use of EUS- FNA of the peritoneum in five patients with decompensated cirrhosis, in whom the diagnosis could not be confirmed by other means; thus, we propose EUS-FNA of the peritoneum as a new, safe, and unexplored technique for diagnosis of peritoneal TB.